PEMBAHARUAN PENDIDIKAN ISLAM: REKONSTRUKSI PEMIKIRAN SEYYED HOSSEIN NASR TENTANG PENDIDIKAN DAN FITRAH MANUSIA - Shidqiyah, Shidqiyah (Reflektika, 2024)
Human morality is an extended reflection to which the educational process influences daily behavior. Islamic education aims to produce output that is intelligent and moral. Implementation of Islamic education in accordance with the modern era requires inspired thought, such as  Seyyed Hossein Nasr thought. This article examines Seyyed Hossein Nasr's paradigm of islamic education. Idea that is based on absolutism tries to revive spirit in building an existence by becoming a perfect human being armed with knowledge. Muslim have to open to knowledge without compartmentalizing knowledge. This study is qualitative of literature review and seeks to describe the findings of data from any relevant literature. Researchers in collecting relevant data examined primary data sources on various journals, books and other related documents that discuss Seyyed Hossein Nasr's thoughts on Islamic education. The data are analyzed in narrative form. This study finds the result, namely the reconstruction of the thought of Seyyed Hossein Nasr who offers an Islamic education system by integrating the knowledge of 'aqli anda naqli. Islamic education in this modern era has to develop without leaving traditional values. Human nature has connectivity with God, human self, and nature (environment). Spirit of eco-theology and Scientia Sacra is quite appropriate and strives for human nature as a trustworthy caliph. Seyyed Nasr offers that human idea connectedness as a caliph must have provision of wisdom obtained through the process of Islamic education. Therefore, nowadays the educational institutions have to adopt an education system that focuses on human development with modern and traditional knowledge.